Metode dan Teknis Analisis Laporan Keuangan (Studi Kasus PT Mandom Indonesia Tbk) - Dani Iwan Saputra; Fanisa Eka Pratiwi; M. Farhan Reza Ridho Kholik; Nabila Imanina Fahira; Ersi Sisdianto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This type of research is qualitative descriptive research. The objectives of this research are (1) To determine and analyze financial performance based on vertical analysis of PT. Mandom Indonesia, Tbk, (2) To determine and analyze financial performance based on horizontal analysis of PT. Mandom Indonesia Tbk. The population in this study is the financial statements of PT. Mandom Indonesia Tbk for 20 years with a sample of 7 years. Results of vertical analysis of PT's balance sheet report. Mandom Indonesia, Tbk from 2015-2021 has been optimal. This can be seen from the total assets post which is greater than the total liabilities post. As for the vertical analysis of the profit and loss report, it shows that it is less than optimal because the amount of operating expenses has increased significantly and affects operating profits. It can be concluded that the financial performance of PT. Mandom Indonesia, Tbk optimal. And the results of the horizontal analysis of PT's balance sheet report. Mandom Indonesia, Tbk from 2015-021 experienced a negative trend in its total assets, because it decreased every year. In the total liabilities and equity of PT. Mandom Indonesia, Tbk also experienced a negative trend because it experienced a decline every year. Then the 2015-2021 profit and loss report showed a negative trend because the company's total revenue experienced a very significant decline. Likewise, operating profit experienced a negative trend due to the increase in expenses being greater than the increase in income, so that based on horizontal analysis the profit and loss report still tends to be less than optimal.